(untitled) (Raparin Journal of Humanities (RJH), 2025)
Nomophobia is defined as the fear or anxiety of being without a mobile phone or cellular service. This condition can lead to symptoms such as agitation, changes in breathing, trembling, and panic attacks. This condition most of the time is associated with the overuse of mobile devices and can significantly affect daily activity and life. While it’s not officially recognized as a disorder but nomophobia is predicted to become common and notifiable in the current digital era. The study’s objectives are to ascertain the degree of nomophobia and social isolation among Raparin University students, as well as any statistically significant differences in these terms among the sample’s students based on factors like gender (male and female), academic year (first, second, third, and fourth), study field (scientific or humanities), and family status (single, married, and divorced). Additionally, the study seeks to ascertain whether nomophobia and social isolation are generally correlated. The research methodology is descriptive. Out of the 4963 students in the study population, 513 students 153 males and 360 females made up the selected sample, which was chosen using suitable random selection and represented around 11% of the total. The questionnaire was used to obtain the data. The 20-item Nomophobia questionnaire, created by Yildirim and Korean (2015), was translated from English into Kurdish, leaving 18 items after modification. The researcher created the 28 items that made up the social isolation scale. One-Way ANOVA, T-Test, and Pearson correlation were the primary statistical methods utilized. The most important results: Students generally have a mild degree of nomophobia، however nomophobia is not observed among the variables (gender، academic year ، and family status) ، while it was observed according to variable of study field and was in favor of the scientific department, and the level of social isolation among students is weak and social isolation wasn’t observed according to the variables (gender, academic year, study field and family status). Social isolation and nomophobia are directly correlated, and the researcher has offered some recommendations and suggestions in light of the research findings.